Climate services user needs assessment: Ayeyarwady Delta, Myanmar - Thant, Phyu Sin; Khaung, Ye; Myae, Chan; Quyen, Ho McGrath; Akester, Michael; Hlaing, Khin Thuzar; Giles, James; Swaans, Kees (2024)
This study aims to bridge the knowledge gap in understanding farmers' diverse information needs for informed decision-making in the Ayeyarwady Delta. It explores the current and desired use of DCAS+ and other services by analyzing farming systems, decision-making processes, climate information usage, and digital readiness among farmers. The findings offer insights into the potential for DCAS+ development and scaling, informing policies and practices for designing, adopting, and expanding these services to meet farmers' needs. The study concludes by discussing the implications and recommendations for integrating DCAS+ in priority farming systems and contributing valuable insights for the design of comprehensive climate advisory services that extend beyond mere weather forecasts but include complementary services to address resource and information constraints